Resonance-like structure observed in ²⁵Mg(p; γ)²⁶Al reaction - Kachan, A.S.; Kurguz, I.V.; Mischenko, V.M.; Utenkov, S.N. (Вопросы атомной науки и техники, 2017)
The γ decay of the resonance-like structure (RLS), observed in the ²⁵Mg(p; γ)²⁶Al in the region of excitation energies of 7...9 MeV was studied. The excitation function of the ²⁵Mg(p; γ)²⁶Al reaction was measured. The resonance strengths in the accelerated proton energy range of Eₚ = 1.4...2.0 MeV were determined. The obtained distributions of the strength of M1 transitions between the resonance states and the low-lying bound states in ²⁶Al have resonance character. The position of the center of gravity of the magnetic dipole resonance (MDR) on the ground state is equal to 7.92 MeV . Total strength MDR in ²⁶Al is equal to 5.7 MeV μ²ₙ. Вивчено γ-розпад резонансноподібної структури (РПС), що спостерігається в реакції ²⁵Mg(p; γ)²⁶Al в районі енергій збудження 7…9 МеВ. Проведено вимірювання функції збудження даної реакції. Сили резонансних станів визначені в інтервалі енергій прискорених протонів Eₚ = 1.4...2.0 МеВ. Отримані розподіли сили М1 переходів між резонансними станами і низьколежачими пов'язаними в ²⁶Al мають резонансний характер. Положення центра ваги магнітного дипольного резонансу (МДР) на основному стані дорівнює 7,92 МеВ. Повна сила МДР дорівнює 5,7 МеВ μ²ₙ. Изучен γ-распад резонансноподобной структуры (РПС), наблюдаемой в реакции ²⁵Mg(p; γ)²⁶Al в районе энергий возбуждения 7…9 МэВ. Проведены измерения функции возбуждения данной реакции. Силы резонансных состояний определены в интервале энергий ускоренных протонов Eₚ = 1.4...2.0 МэВ. Полученные распределения силы М1 переходов между резонансными состояниями и низколежащими связанными в ²⁶Al имеют резонансный характер. Положение центра тяжести магнитного дипольного резонанса (МДР) на основном состоянии равно 7,92 МэВ. Полная сила МДР равна 5,7 МэВ μ²ₙ.